KOMPOSISI DAN STRUKTUR VEGETASI POHON SEBAGAI PENYIMPAN CADANGAN KARBON DI HUTAN DAN TAMAN KOTA PEKANBARU UNTUK PENGEMBANGAN MODUL KONSEP MANFAAT HUTAN PADA MUATAN LOKAL PENDIDIKAN LINGKUNGAN HIDUP KELAS XI DI SMAN 1 PEKANBARU - Ade Diana Kharisma; Sri Wulandari; Nursal ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The research was conducted to determine the composition and structure of vegetation of trees and carbon stocks in forests and city parks Pekanbaru in November 2015 to January 2016. The results used to develop module concept of forest benefits on local content of environmental education high school grade XI. The study consisted of two phases, the first analysis of the composition, vegetation structure, and estimation of carbon stocks with the survey and non - destructive method. The second phase, developing a module with concept of forest benefits by using ADDIE models. Based on the survey results revealed that the forests and parks of Pekanbaru there are 21 family, 48 species and 3218 trees with an average density of 500.64 trees / ha and diversity index of 1.93 is classified as moderate. Total carbon stocks in forest and city park of Pekanbaru is 325.692 tons. The results of the research used to development of modules and get very valid with a mean value of 4.25 and a limited test results get very good category with a mean of 85.42.Keywords : Carbon Stock, species composition, vegetation structure tree.